Eksistensi Pendidikan Agama Hindu di Era Digital Dalam Memperkuat Karakter Siswa - Sukerni, Ni Made; Arini, Ni Wayan (Jayapangus Press, 2023)
The rapid development of technology in the digital era is one of the challenges in developing children's character today. Technology has had an impact in terms of the decline in children's character values. Therefore, Hindu religious education is very important in this situation to help students understand and overcome the moral dilemmas that occur in the digital world. This research aims to determine the efforts that need to be made to strengthen student character in the digital era. This research uses a qualitative type of research using a descriptive analysis approach. The results of this research indicate that cyber technology can be used to create learning strategies that encourage students to learn independently, and the character of education must be consistently included in all Hindu religious learning activities. Apart from school teachers, parents also play an important role in directing children to use technology wisely. The character values ​​that can be instilled in Hindu religious teachings are as follows, religious values, tolerance, discipline, independence, curiosity, friendship/communicativeness, caring for the environment and responsibility.